1998
DOI: 10.1021/jp981689l
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Mechanism of the Addition of Diazomethane to Ethylene and Formaldehyde. Comparison of Conventional ab Initio and Density Functional Methods

Abstract: The 1,3-dipolar cycloaddition reactions of diazomethane with ethylene and formaldehyde as well as the nitrogen elimination reactions from the cycloadducts have been studied using density functional and conventional ab initio methods. The exothermicity of the reactions is underestimated by DFT methods with respect to CCSD(T) due to an overestimation of the C−N dissociation energy of diazomethane. For the cycloaddition reactions all methods lead to similar transition state geometries, and the potential energy ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…Ab initio and DFTcalculations indicate that, in the reaction of diazomethane with formaldehyde, the kinetically most favorable cycloadduct is less stable than the reactants and has a lower barrier for nitrogen elimination [17]. Derivative 22 has been postulated as intermediate in the metabolism of some (2-hydroxyethyl)-or (2-haloethyl)nitrosoureas, a class of highly active antitumor agents (Scheme 13.3) [18].…”
Section: 2-3-oxadiazolinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ab initio and DFTcalculations indicate that, in the reaction of diazomethane with formaldehyde, the kinetically most favorable cycloadduct is less stable than the reactants and has a lower barrier for nitrogen elimination [17]. Derivative 22 has been postulated as intermediate in the metabolism of some (2-hydroxyethyl)-or (2-haloethyl)nitrosoureas, a class of highly active antitumor agents (Scheme 13.3) [18].…”
Section: 2-3-oxadiazolinesmentioning
confidence: 99%
“…For 3-methylsydnone, the 14 N and 17 O spectra have also been determined and a complete set of chemical shift values for all the atoms have been reported [45]. According to a synthetic approach that allowed for the independent labeling of the nitrogen atoms (Section 13.2.5.1), the NMR chemical shift for each 15 N has been determined unambiguously.…”
Section: Nmr Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…Blavins et al computed a DH°( 0K) value of 16.4 kcal mol À1 with the CCSD(T)/6-311 + + GA C H T U N G T R E N N U N G (2d,2p) method, [103] while Branchadell found the barrier to be 13.0 kcal mol À1 using the CCSD(T)/ 6-311G** method. [104] The barrier for fulminic acid with acetylene was also investigated with CCSD(T) and G2 variants. All of the high accuracy methods give essentially the same value as the CBS-QB3 value within 0.5 kcal mol…”
mentioning
confidence: 99%
“…Only in the last decade have several sound computational studies been reported to help understanding the way this reaction occurs. [4][5][6][7][8][9][10][11] Thioisomünchnones (1,3-thiazolium-4-olates or anhydro-4-hydroxy-1,3-thiazolium hydroxides) constitute a group of mesoionic heterocycles that behave as masked dipoles in 1,3-dipolar cycloadditions due to their thiocarbonyl ylide Scheme 1.…”
Section: Introductionmentioning
confidence: 99%